1995
DOI: 10.1002/chem.19950010308
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of H2S with SO2: Molecular Structures, Energies, and Vibrational Data of Seven Isomeric Forms of H2S3O

Abstract: High-level a b initio MO calculations (MP2/6-31 lG**//MP2/6-31 lG**) on 16 isomeric forms of H,S,O (including rotamers) have been performed. The nonhelical hydroxotrisulfane HOSSSH 1 a (motif + + -) is the most stable isomer, while the chains with motifs + + + and + -+ are less stable by 1.7 and 3.7 kJmol-', respectively. The other isomers of H,S,O increase in energy in the order HSS(0)SH < HOS(S)SH < HSOSSH < HS(0)SSH < HS(S)SOH < HS(S)OSH.The trisulfane-2-oxide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…1 shows the optimized structures of the selected acids in the gas phase. As mentioned before, there are several isomers for each sulfur oxoacid (neutral, mono-and dianion) [15][16][17][18][19][20][21][22]35,36 and the most stable isomer (lowest Gibbs free energy) for each species was selected for the geometry optimization in this work. For example, Steudel and Otto 18 have studied the stabilities of different isomers for H 2 S 2 O 3 and H 2 SO 5 along with their monoanions in the gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…1 shows the optimized structures of the selected acids in the gas phase. As mentioned before, there are several isomers for each sulfur oxoacid (neutral, mono-and dianion) [15][16][17][18][19][20][21][22]35,36 and the most stable isomer (lowest Gibbs free energy) for each species was selected for the geometry optimization in this work. For example, Steudel and Otto 18 have studied the stabilities of different isomers for H 2 S 2 O 3 and H 2 SO 5 along with their monoanions in the gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…For example, aqueous calcium sulfate (CaSO 4 ) was observed to have the slowest rate of reduction, followed by calcium sulfite (CaSO 3 ), and then by elemental sulfur (S 8 ) as the most reactive . Depending on the pH conditions of the environment, sulfur in the S(IV) state also occurs as SO 2 , and previous theoretical studies have identified a reaction mechanism for the reduction of SO 2 (S(VI)) to S 8 (S(0)) with a maximum energy barrier of only $36.5 kcal mol À1 (Drozdova and Steudel, 1995;Sendt and Haynes, 2005). These results indicate that the reduction of S(VI) to S(IV) is likely to be the rate limiting step in the overall pathway of reduction of sulfate to sulfide.…”
Section: Theoretical Models and Computational Methodsmentioning
confidence: 99%
“…Derivatives of the sulfanes like the sulfane oxides HϪSϪSϪOH [28] and HϪSϪS(O)ϪSϪH [29] will probably be similarly strong acids in the vapor phase. Therefore, the dissociation of H 2 S 2 requires much less Gibbs free energy than that of H 2 S and the dissociation of H 2 S 3 requires less than that of H 2 S 2 and so forth.…”
Section: Hsmentioning
confidence: 99%